1997
DOI: 10.1029/97jd00931
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tropospheric OH radicals by long‐path differential‐optical‐absorption spectroscopy: Experimental setup, accuracy, and precision

Abstract: Abstract. This paper describes a newly developed long-path differential-optical-absorptionspectroscopy instrument used for the measurement of tropospheric OH radicals. The instrument consists of a high resolution echelle spectrometer in conjunction with a multiple-reflection cell of 38.5 m base length and a UV laser light source that provides a spectral line width of 0.41 nm. Local in situ absorption measurements at total path lengths of either 1.85 or 3.1 km can be performed. The simultaneous observation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…The Multichannel Scanning Technique (MCST) is used to reach the required signal to noise ratio . One air spectrum is recorded within 135 s. A comparison of measured and modelled MCST spectra is given by Hausmann et al (1997) who found a maximum 1.7% error contribution to the accuracy of the measurement. The deconvolution of the measured spectrum is performed by fitting a trigonometric background consisting of 16 terms and three reference spectra, namely OH, HCHO, and an so far unidentified absorber X (Schlosser et al, 2006).…”
Section: High-resolution Doas Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Multichannel Scanning Technique (MCST) is used to reach the required signal to noise ratio . One air spectrum is recorded within 135 s. A comparison of measured and modelled MCST spectra is given by Hausmann et al (1997) who found a maximum 1.7% error contribution to the accuracy of the measurement. The deconvolution of the measured spectrum is performed by fitting a trigonometric background consisting of 16 terms and three reference spectra, namely OH, HCHO, and an so far unidentified absorber X (Schlosser et al, 2006).…”
Section: High-resolution Doas Instrumentmentioning
confidence: 99%
“…An effective cross section for broad-band-DOAS can be calculated using any of these cross sections by convolution with an appropriate instrument function. For the high-resolution DOAS (HR-DOAS) instrument designed to detect tropospheric OH radicals (Hausmann et al, 1997;Brauers et al, 2001;Schlosser et al, 2006) no literature data at sufficiently high spectral resolution (2.7 pm) is available. However, a comparison between the highest resolution literature data of Smith et al (2006) and the HR-DOAS data is given in the discussion of this paper .…”
Section: Introductionmentioning
confidence: 99%
“…Only one instrument currently exists for atmospheric OH detection, which is installed in the atmosphere simulation chamber SAPHIR in Jülich. Details of the instrument can be found elsewhere (Hausmann et al, 1997;Schlosser et al, 2007Schlosser et al, , 2009.…”
Section: Oh Detection By Doasmentioning
confidence: 99%
“…It provides inherently calibration-free measurements of tropospheric OH radicals with an 1σ accuracy of 6.5 % (Hausmann et al, 1997) and is therefore accepted as a reference technique for OH. Besides OH, also formaldehyde, sulfur dioxide, and naphthalene can be simultaneously detected.…”
Section: Differential Optical Absorption Spectroscopy (Doas)mentioning
confidence: 99%
“…Besides OH, also formaldehyde, sulfur dioxide, and naphthalene can be simultaneously detected. Details of the instrument can be found elsewhere (Hausmann et al, 1997;Schlosser et al, 2007Schlosser et al, , 2009. The output of a dye laser (616.08 nm, pulse duration 800 fs) is frequency doubled in an external BBO crystal to generate broad-band UV radiation at 308.04 nm with a bandwidth of approximately 0.5 nm.…”
Section: Differential Optical Absorption Spectroscopy (Doas)mentioning
confidence: 99%